Introduction to The Print in the Codex - Jeanne-Marie Musto (Journal of Art Historiography, 2022)
arah Schaefer’s study of nineteenth-century Bibles is the first of two papers from a session held at the 2021 College Art Association Annual Conference that will appear in this journal. Entitled ‘The Print in the Codex’ and sponsored by the Bibliographical Society of America, the session considered books transformed through the incorporation of independently printed images. In tracing the transformation of extra-illustration into standardized illustration, Schaefer provides significant insights for both book and print history. In the next issue of this journal, a paper by Sylvia Massa will consider codices created to house single-sheet prints. The integration of these codices into public collections has frequently meant removing the prints from the bindings altogether and, thereby, removing their historical context. Focusing on developments at the Kupferstichkabinett in Berlin, her paper sheds light on an overlooked aspect of book and print history of importance to both curators and print historians.